Adsorption Characteristics of Trace Volatile Organic Compounds on Activated Carbon Fibres at Room Temperature - Zheng-Hong Huang; Feiyu Kang; Yong-Ping Zheng; Jun-Bing Yang; Kai-Ming Liang (Adsorption Science & Technology)
The adsorption characteristics of volatile organic compounds (VOCs) on viscose rayon-based activated carbon fibres (ACFs) were investigated. ACFs with specific surface areas of 640 m 2 /g and 1460 m 2 /g were used to adsorb trace volatile organic compounds in nitrogen streams at atmospheric pressure at or near room temperature (25°C and 30°C). The experimental results showed that ACFs with different surface areas exhibited different dynamic adsorption behaviours at or near room temperature.